The global prevalence of low back pain in pregnancy: a comprehensive systematic review and meta-analysis - Nader Salari; Aida Mohammadi; Mahvan Hemmati; Razie Hasheminezhad; Salim Kani; Shamarina Shohaimi; Masoud Mohammadi (BMC, 2023)
Abstract Background Back pain during pregnancy is often considered as an unavoidable problem and can reduce the quality of life or disability of pregnant women. The aim of this study is to determine the global prevalence of back pain in pregnancy based on a systematic review and meta-analysis. Methods In this study, Researchers systematically searched electronic databases PubMed, Scopus, Web of Science, Embase, ScienceDirect, and Google Scholar search engines for studies until September 2023. To analyze data, the random effects model was used, and the heterogeneity of the studies was checked with the I2 index. Data analysis was performed by software (Version 2 Comprehensive Meta-Analysis). Results In the review of 28 studies with a sample size of 12,908 people, the I2 heterogeneity test showed high heterogeneity (I2: 98.4). Based on this, the random effects method was used to analyze the results. Therefore, the meta-analysis reported the global prevalence of back pain at 40.5 (95% CI: 33-48.4) during pregnancy. Also, according to the meta-analysis, the global prevalence of back pain in the first trimester of pregnancy is 28.3 (95%CI: 10.5-57.1), in the second trimester is 36.8 (95%CI: 30.4-43.7) and in the third trimester of pregnancy was reported as 47.8 (95% CI: 37.2-58.6). Conclusion In this meta-analysis, the overall prevalence of back pain in pregnant women was reported to be significant, so it is necessary for health policymakers to pay more attention to complications during pregnancy, in addition to increasing society's awareness of pregnant mothers, with timely diagnosis and treatment of such disorders, it can lead to improvement; and reduction in Complications caused by pregnancy and becoming more pleasant during pregnancy.